Utilization of Agricultural and Organic Waste as Eco-Friendly Biomass-based Adsorbents - Pujiastuti, Hendrini; Aziz, Sarah Rafidah (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2025)
The development of effective and sustainable remediation techniques is required due to the growing environmental contamination brought on by industrial activities, especially from heavy metals and organic pollutants. The purpose of this review is to evaluate critically the potential of biomass-based adsorbents made from organic and agricultural waste for use in environmental remediation, specifically in the treatment of soil and water. The study assesses the surface properties, functional groups, and adsorption mechanisms of several bio-adsorbents and groups them according to their sources, including activated carbon, agricultural residues, and biochar. The impact of chemical and physical changes on improving adsorption performance is also thoroughly examined. The results show that these environmentally friendly materials have notable adsorption capacities and provide a sustainable, scalable, and affordable substitute for traditional synthetic adsorbents. The study adds to the expanding corpus of research that supports the circular economy's waste valuation principles and emphasises the usefulness of green environmental management techniques.